CHINA`S ECONOMIC INTEREST IN KENYA - Bandurina, Olena (Revista JRG de Estudos Acadêmicos, 2021)
This article focuses on China`s economic interest in Africa: Case Study of Kenya. Basically the article will be examining several specific objectives: composition and sectors of Chinese Foreign Direct investments in Kenya particularly in the sphere of infrastructure and telecommunication, the significance and volume of trade imbalance, the economic and social impact of Chinese investments in Kenya and the possible recommendations towards the improvement of social, political and economic development in Kenya. The case study research raises several research questions. What are the economic and social impact of Chinese investments in Kenya? What could be done to improve social, political and economic development in Kenya? In which way should Kenya restructure its policy towards China?